Effect of Hydrogel Nanocomposites on the Fresh and Hardened Properties of Cementitious Pastes - Siqueri, Vitor A. S. [UNESP]; Filho, Adhemar W. [UNESP]; de Moura, Marcia R [UNESP]; Aouada, Fauze A. [UNESP] (Wiley, 2020)
Cement is a material widely used in civil construction due to its physical and chemical properties, ensuring a good performance. Some polymeric materials, such as hydrogels, have been frequently added to improve these properties and mitigate autogenous retraction in cementitious matrices. This paper aimed to evaluate the influence of polymeric hydrogel on the fresh and hardened properties of cementitious pastes (water/binder ratio = 0.35). Fresh properties results showed that the consistency and exudation indexes of these matrices decreased with an increase in the amount of hydrogel. The values of the bulk density of all cementitious matrices are around 2.1–2.2 g cm−3. Matrices containing up to 1.0% of hydrogel have satisfactory mechanical properties, reaching compressive strength of 60 MPa for 112 days of curing age. From these results, it is possible to conclude that hydrogels are promising materials for civil engineering applications, acting mainly as a filler and hydroretentor agent.
Keywords: civil construction; hydrogel; mechanical properties; nanoclay; structural composite